Pembuatan Biodiesel Dari Minyak Biji Bintaro Dengan Reaksi Transesterifikasi Dan Katalis Lempung - Ratna Dian Armalita; Syaiful Bahri; Yusnimar Yusnimar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Biodiesel is one of the alternative energy made from the transesterification reaction between vegetable oils and methanol. One potential source of vegetable oil to be developed in Indonesia is bintaro seed oil. Plant bintaro as a non-food crop so it will not compete with food needs as well as cultivated plants are now widely used as an ornamental plant reforestation and on the edge of the highway. This study aims to create crude biodiesel from oil of the seeds bintaro. In this study the effect of amount of clay catalyst (0.5%, 1%, 1.5%) and effect of the mole ratio of methanol-oil (3: 1, 6: 1 , 9: 1) are studied in biodiesel produced and determined the characteristics of biodiesel from oil seeds bintaro. The study begins from raw material preparation which includes drying and grinding. Furthermore, bintaro seed oil is extracted and followed by degumming to remove impurities contained in the oil. Acquisition of the highest of crude biodiesel yield obtained by 91.70% in conditions reactan is ratio of 9 : 1 and amount of catalyst 0.5%. Results characteristics of crude biodiesel such as density 40oC of 890 kg/m3, 4.7 cSt viscosity kinematic 40oC, acid number of 0.59 mg-KOH/g. Based on analysis of GC-MS (Gas Chromatography-Mass Spectromatry) shows that the composition of crude biodiesel are methyl Oleat bintaro 53.92%, 25.91% methyl palmitate and methyl linoleic 20.16%.Keyword : biodiesel, clay, bintaro seed oil